On the Structure of Interior KU-algebras and KU-ideals - Almuhaimeed, Areej (Communications in Mathematics and Applications, 2023)
In this paper, the notation of interior KU-algebra and some related definitions are introduced. Various characterisations for the interior KU-algebra have been proved. The concept of interior positive implicative KU-algebra and prove some results regarding this concept are also presented. In addition, the interior KU-ideals and several properties of these ideals are presented.